Metatropic dysplasia lethal variants - ELÇİOĞLU, HURİYE NURSEL (SPRINGER, 2004)
Background: The metatropic dysplasia group includes fibrochondrogenesis, Schneckenbecken dysplasia and metatropic dysplasia (various forms). The overlapping features of this group with other dysplasias may cause diagnostic confusion, particularly in perinatal lethal cases. Objective: To attempt to classify the radiological findings of the presented eight sporadic cases based on a broad review of the perinatally lethal metatropic group of conditions and to discuss some overlapping features in the light of current knowledge. Results: The first four cases are of recognised conditions, namely lethal metatropic dysplasia (Type 2) or hyperchondrogenesis, lethal hyperplastic metatropic dysplasia (Type 1) and fibrochondrogenesis. The remaining four cases cannot be categorised accurately and are different from each other but with some features of the metatropic group of dysplasias. Conclusions: The dysplasias within the metatropic dysplasia group are phenotypically distinct from many forms of chondrodysplasia but the pathogenesis still remains poorly understood from the morphological and molecular perspectives. Chondro-osseous morphology might be helpful in all lethal cases especially in our last four cases.
Keywords: skeleton; congenital; dysplasia; metatropic dysplasia; hyperchondrogenesis; fibrochondrogenesis; lethal osteochondrodysplasia; neonate; child; FIBROCHONDROGENESIS; DWARFISM; CHONDRODYSPLASIA; FEATURES